Sustained virological response (SVR) and safety of two direct acting anti-viral (DAA) combination therapies in Chronic Hepatitis-C infected patients of Lahore, Pakistan. A Randomized Controlled Trial: SVR and DAA Therapies in Hepatitis-C Infected Patients - Kazmi, Salman; Farooqi, Humaira; Sohail, Umer; Haider Zaidi, Sohaib; Majeed, Naeem; Firdus, Safia (Pakistan Journal of Health Sciences, 2022)
Chronic Hepatitis C (HCV) is a deadly infection affecting > 185 million people worldwide and led to liver cirrhosis, hepatocellular carcinoma, or liver failure. Recently, treatment regimens of chronic HCV have entered the era of direct acting anti-virals (DAAs). Sustained virological response (SVR) rate is one of the best available tools to evaluate the efficacy of DAA treatments. Objective: To compare SVR rate and safety of two combinations of DAA treatments (Sofosbuvir and Daclatasvir vs Sofosbuvir and Velpatasvir) in chronic HCV infected patients of Lahore, Pakistan. Methods: Present randomized controlled trial was conducted at Mayo Hospital, Lahore, Pakistan and recruited 76 chronic HCV infected patients according to Consort guidelines. Registered patients were allocated in two groups by lottery method. Group A received sofobuvir with daclatasvir (SOFO + DCV) while group B received sofobuvir with velpatasvir (SOFO + VEL) treatment for 12 weeks. Response to therapy was evaluated in terms of SVR after 24 weeks and safety profile of the drug. Results: Both treatment groups showed high SVR 24 weeks after the completion of therapy. Group A (SOFO + DCV) presented 92% SVR while group B showed 97% SVR rate. Both DAA combination therapies presented good efficacy and safety profile. Few contraindications noted during the treatment included fatigue, arthritis, headache, loss of appetite and anemia. Conclusions: The efficacy of both DAA combination therapies was comparably high with > 90% SVR rate. Group A proved safer as compared to group B. Studied DAA combinations are effective treatment options for chronic HCV treatment planning.